Retrospective Analysis of the Pattern, Causes and Variants of Ocular Herpes Severity - G. M. Chernakova; G. Sh. Arzhimatova; E. V. Shirshova; A. V. Andrianova; E. A. Kleshcheva; N. V. Mel’nikova (Oftalʹmologiâ)
Purpose: to determine the variants of the severity of the course of ophthalmic herpes on the extensive retrospective material.Material and methods. A retrospective cohort multicenter study was conducted from 2010 to 2020 inclusive. Medical outpatient records and case histories of inpatients were studied. 1142 patients with the following diagnoses were included in the retrospective analysis: “herpetic keratitis”, “recurrent corneal erosion”, “herpetic keratoveitis”, “herpetic corneal ulcer”, “herpetic iridocyclitis”, of which 470 (41 %) were men and 672 (59 %) were women. The mean age was 44.1 ± 1.3 years. Subjects analyzed were: clinical form of ophthalmic herpes; record of primary ophthalmic herpes case or relapse, total timing of complaints, doses of systemic therapy with nucleoside analogs; total timing of episode treatment and record of ophthalmic herpes outcomes in completed cases; presence/absence of trigger factors; presence/absence of manifest comorbid diseases/conditions/events. The localization and frequency of extraocular herpes were recorded. The variant of laboratory confirmation of herpetic etiology of ocular inflammation, if present, was noted.Results. The specific weight of clinical forms of ophthalmic herpes (according to the results of retrospective analysis): epithelial forms — 263 patients, stromal forms — 650, anterior uveitis — 229. In the majority of cases (n = 799; 70 %) patients had a history of recurrent course of keratitis (keratouveitis) by the time of initial examination, whereas first detected ophthalmic herpes was noted in 343 (30 %) cases. Depending on the duration of active complaints the patients were distributed as follows: with complaints from 1 day to 1 month — 113 (10 %), from 2 to 3 months — 517 (45 %), from 3 to 6 months — 272 (24 %), from 6 months and more — 240 (21 %). The mean duration of complaints was 64.5 ± 6.5 days. Epithelial keratitis has the least tendency to form a protracted course: in more than a half of cases (192 patients out of 263) the period of complaints did not exceed 3 months. Among 1142 patients there were 235 completed cases of keratitis and keratouveitis (20.5 %) with remission. The most frequent (422 cases) provoked ophthalmic herpes was different systemic infectious processes. The second place by the frequency of provoking factors is occupied by a group of causes related to corneal damage of different genesis (285 patients). In the third place by frequency are emotional or physiologic stresses. Next in frequency of ophthalmic herpes provocation are problems of the middle zone of the face — 240 cases. Manifest infectious-inflammatory diseases of the nasopharynx and respiratory tract are leading among background conditions (753 patients). The second place among the causes of comorbidity is occupied by cumulative immunosuppression (n = 217). In the third place by the frequency of comorbid pathology are gastrointestinal diseases — 126 patients (11 %). Herpesvirus etiology was investigated by ELISA in 546 (48 %), in the other 52 % — not confirmed by any laboratory method.Conclusion. As a result of the conducted study, a significant cohort of patients with characteristics of ophthalmic herpes of severe course was identified: deep forms of ocular tissue lesions, prolonged duration of complaints, recurrent forms. These characteristics were accompanied by the use of low (not more than 1.5 g) daily doses of oral nucleoside analogs. Division of patients by severity of ophthalmic herpes course into mild and severe forms may allow to distinguish a cohort of patients requiring deeper diagnostic examination, consultations of related specialists, as well as higher daily doses of systemic antiviral therapy. Given that herpesvirus etiology has not been confirmed or investigated by ELISA, the development of clear diagnostic criteria through the use of molecular biological methods is necessary. The dominance of such comorbid diseases as sinusitis and tonsillitis (66 %) dictates the need to study the state of the paranasal sinuses in ophthalmic herpes of severe course.